2020
DOI: 10.1016/j.molcel.2020.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Insulin- and Lipopolysaccharide-Mediated Signaling in Adipose Tissue Macrophages Regulates Postprandial Glycemia through Akt-mTOR Activation

Abstract: Highlights d Feeding elevates serum LPS and insulin, which induce IL-10 in macrophages in vitro d Insulin and LPS/insulin-treated macrophage medium suppress gluconeogenic genes d Myeloid IL-10-deficient mouse models show dysregulated postprandial glycemia d IL-10 expression in obese mice restores postprandial gluconeogenic gene suppression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…Lu et al have identified artemether as an activator of browning and thermogenesis in vitro, which significantly enhances the metabolism of mice, as indicated by the insulin tolerance test (ITT) and glucose tolerance test (GTT) results (Lu et al, 2016). To further evaluate the pharmacological potential, Lu et al found that artemether and other artemisinin derivatives induce C3H10T1/2 cell browning by activating the p38 mitogen-activated protein kinase (MAPK)/activating transcription factor-2 (ATF2) axis and deactivating the Akt/ mTOR pathway, which has suggested to be involved in various anabolic and catabolic processes (Cai et al, 2016;Lu et al, 2016;Fischer et al, 2020;Toda et al, 2020). Moreover, onestep qPCR suggested that the relative mRNA levels of browningrelated genes, such as PR domain containing 16 (PRDM16), uncoupling protein 1 (UCP1) and peroxisome proliferatoractivated receptor γ coactivator-1α (PGC-1α), were elevated after treatment with artemether, indicating that the increased thermogenesis in brown fat may also cause weight loss and enhance the metabolism in artemether-treated mice (Lu et al, 2016).…”
Section: Activation Of Brown Fat and Browning Of White Fatmentioning
confidence: 99%
“…Lu et al have identified artemether as an activator of browning and thermogenesis in vitro, which significantly enhances the metabolism of mice, as indicated by the insulin tolerance test (ITT) and glucose tolerance test (GTT) results (Lu et al, 2016). To further evaluate the pharmacological potential, Lu et al found that artemether and other artemisinin derivatives induce C3H10T1/2 cell browning by activating the p38 mitogen-activated protein kinase (MAPK)/activating transcription factor-2 (ATF2) axis and deactivating the Akt/ mTOR pathway, which has suggested to be involved in various anabolic and catabolic processes (Cai et al, 2016;Lu et al, 2016;Fischer et al, 2020;Toda et al, 2020). Moreover, onestep qPCR suggested that the relative mRNA levels of browningrelated genes, such as PR domain containing 16 (PRDM16), uncoupling protein 1 (UCP1) and peroxisome proliferatoractivated receptor γ coactivator-1α (PGC-1α), were elevated after treatment with artemether, indicating that the increased thermogenesis in brown fat may also cause weight loss and enhance the metabolism in artemether-treated mice (Lu et al, 2016).…”
Section: Activation Of Brown Fat and Browning Of White Fatmentioning
confidence: 99%
“…In this issue of Molecular Cell, Toda et al (2020) show that postprandial elevation of LPS and insulin induce the production of IL-10 by adipose tissue macrophages. Hepatic gluconeogenesis is then inhibited synergistically by insulin and IL-10 to facilitate glucose clearance.…”
mentioning
confidence: 94%
“…In light of the vast complexity of the immuno-metabolism network, which so far has been shown to be highly dependent on experimental conditions, it is evident that rigorous analysis of macrophage biology is required to understand the influence of nutrition on the immune system. In this issue of Molecular Cell, Toda et al (2020) demonstrate the direct involvement of ATMs in regulating postprandial hepatic gluconeogenesis through interleukin-10 (IL-10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In obese humans, IL10 expression in WAT was inversely associated with insulin resistance (Mclaughlin et al, 2014). Interesting, adipocytes are able to modulate immune responses in the spleen, including IL10 production (Vielma et al, 2013;Toda et al, 2020). Moreover, WAT depots also represent an abundant source of IL10 in the context of viral infections (Garcia-Valtanen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%